The Fourth K : A Novel - Puzo, Mario, 1920-1999 (New York Bantam Books, 1991)
When a terrorist targets his daughter, President Francis Xavier Kennedy responds with bloody decision.
Keywords: Presidents -- Political crimes and offenses -- Suspense fiction -- English fiction -- Politics and government